Potential impacts of silver nanoparticles on bacteria in the aquatic environment. (15th April 2017) - Sheng, Zhiya; Liu, Yang
Abstract: It is inevitable that nano-silver will be released into the environment. Therefore, there is an urgent need to better understand the effects of silver nanoparticles (Ag-NPs) on microbes in natural and engineered environments. The most remarkable gap in our knowledge on this lies on the low Ag-NPs dose side. This review summarized studies on the effects of Ag-NPs on bacteria from simple to complicated aquatic systems. A hormetic model with a narrow stimulatory zone has been proposed based on both experimental phenomenon and the potential mechanisms of the observed effects. Spectrum of the stimulating zone depends on Ag-NP properties, bacterial types and environmental conditions tested. This may become a concern in terms of Ag-NP disposal, and further research is required to build a sophisticated toxicity model for Ag-NPs. Highlights: The dose-response of bacteria to Ag-NPs may conform to the hormetic model. Ag-NPs toxicity on bacteria is dependent on Ag-NP properties, bacterial types and environmental conditions. Mixed cultures such as biofilm and sludge are more resistant to Ag-NPs compared with pure culture. Higher microbial diversity often results in higher Ag-NP resistance.